Artificial Intelligence and Faith: Impacts of Emerging Technologies on Christian Doctrine and Belief Systems - Babalola , Janet Modupe (Corpus Intellectual, 2025)
The rapid growth of artificial intelligence (AI) technologies creates new opportunities and difficulties in various fields, including religion. This study investigates the complex relationship between AI and Christian religion, emphasising how emergent technologies impact Christian doctrine and belief systems. This study examines how AI-powered tools and activities affect Christian communities by examining theological perspectives, doctrinal interpretations, and ethical concerns. The paper begins by looking at historical relationships between Christianity and technology, which provides background for understanding the contemporary AI revolution. It then dives into specific areas where AI overlaps with Christian concepts, such as automated decision-making in ethical quandaries, AI-driven biblical exegesis, and the application of AI in spiritual formation and pastoral care. The study examines these intersections critically, highlighting both the benefits AI provides for strengthening faith and the potential hazards it poses to traditional beliefs. Furthermore, the study discusses the ethical implications of AI in light of Christian beliefs, focussing on questions of free will, human dignity, and the existence of the soul. It also analyses how artificial intelligence (AI) may challenge or reinforce existing theological frameworks and whether specific components of Christian doctrine must be rethought. Finally, this study provides a unique viewpoint on integrating AI into Christian life, providing ways for believers and theologians to engage with these developing technologies while keeping grounded in their faith. The findings add to a more extensive discussion on the role of AI in changing the future of religious belief and practice, giving valuable insights for academics and the Christian community.